Acid–Base Free Main Group Carbonyl Analogues. (19th October 2020) - Loh, Ying Kai; Aldridge, Simon
Abstract: Main group carbonyl analogues (R2 E=O) derived from p‐block elements (E=groups 13 to 15) have long been considered as elusive species. Previously, employment of chemical tricks such as acid‐ and base‐stabilization protocols granted access to these transient species in their masked forms. However, electronic and steric effects inevitably perturb their chemical reactivity and distinguish them from classical carbonyl compounds. A new era was marked by the recent isolation of acid–base free main group carbonyl analogues, ranging from a lighter boracarbonyl to the heavier silacarbonyls, phosphacarbonyls and a germacarbonyl. Most importantly, their unperturbed nature elicits exciting new chemistry, spanning the vista from classical organic carbonyl‐type reactions to transition metal‐like oxide ion transfer chemistry. In this Review, we survey the strategies used for the isolation of such systems and document their emerging reactivity profiles, with a view to providing fundamental comparisons both with carbon and transition metal oxo species. This highlights the emerging opportunities for exciting "crossover" reactivity offered by these derivatives of the p‐block elements. Abstract : Recently, hitherto elusive acid‐ and base‐free main group carbonyl analogues (R2 E=O) derived from group 13 to 15 elements have been isolated in crystalline form. Their unperturbed nature elicits exciting new chemistry, spanning the vista from classical organic carbonyl‐type reactions to transition metal‐like oxide ion transfer chemistry.